Components of fecundity and abortion in a tropical tree, Dahlstedtia pentaphylla (Leguminosae) - Teixeira, Simone de Pádua; Pereira, Rodrigo Augusto Santinelo; Ranga, Neusa Taroda [UNESP] (Brazilian Archives of Biology and Technology, 2006)
Este trabalho estudou o efeito dos componentes de fecundidade na reprodução de Dahlstedtia pentaphylla, leguminosa neotropical com baixa produção de frutos e sementes. Para tal, foram analisadas as relações das posições das flores na inflorescência e dos óvulos/sementes no ovário/fruto ao aborto de frutos e sementes. Não ocorreram diferenças na deposição de pólen em flores e na formação de frutos em função da posição na inflorescência. Não se encontrou também relação entre aborto de óvulos/sementes e sua posição no ovário/fruto. A limitação dos recursos maternos aos frutos e aos embriões, devido ao alto custo de formação de frutos e maturação das sementes, foi um dos fatores responsáveis pelas altas taxas de aborto nesta espécie.

Studies were conducted on pollination and patterns of fruit and seed production to assess the potential factors causing high fruit and seed abortion in Dahlstedtia pentaphylla (Leguminosae) through analyses of relationships between flower position in the inflorescence and ovules and seeds within ovaries and fruits, and flower, fruit and seed abortion. No differences were found in pollination and fruit set as a function of inflorescence position. There was no relationship, neither between degenerating ovules and their position within the ovary, nor between developing seed and fruit position. Maternal resource limitation related to fruits and embryos, due to the high cost of fruit production and seed maturation, was one of the factors that led to a high abortion rate in D. pentaphylla.
Keywords: Abortion; Atlantic rainforest; Dahistedtia pentaphylla; Leguminosae; Reproduction